Humoral and cell-mediated immune responses of lambs against bluetongue virus - DESHMUKH, V V; GUJAR, M B (The Indian Journal of Animal Sciences, 2013)
The bluetongue virus (BLU-1) was isolated from field outbreaks in Maharashtra. The Virus was adopted on BHK-21 cell lines. Humoral immune responses of lambs were evaluated by uSing competitive enzyme linked immunosorbent assay (eELISA) and complement fixation test (CFT). The cell-mediated immune response (CMI) was evaluated by using leucocyte migration inhibition test (LMIT). The cell culture adopted BLU. 1 virus was astrong immunogen. The antibody to BLU-1 was produced on seventh day post-inoculation which persisted at high level after challenge infection. The CMI was developed from seventh day post-inoculation and persisted at high level after challenge infection.